528 Advanced echocardiographic assessment in outpatients with advanced heart failure undergoing periodical levosimendan infusion. (8th December 2021) - Morello, Matteo; Miglierina, Emilio; Golino, Michele; Ceriani, Francesca; Oliva, Carlo; Blasi, Federico; Croce, Francesca; Seganfreddo, Francesca; Refujiati, Taulant; Marazzato, Jacopo; De Ponti, Roberto
Abstract: Aims: The long-term clinical effects of Levosimendan in patients (pts) with heart failure and reduced ejection fraction (HFrEF) are mainly mediated by its long-acting metabolite, OR-1896, whose half-life is much longer (81 h vs. 1–1.5 h), although with similar inotropic and vasodilatory effect. Echocardiographic data are still lacking, expecially in the chronic setting. Global longitudinal strain (GLS) and left ventricular myocardial work index (LVMWI) are novel non-invasive methods for left ventricle (LV) function evaluation that consider myocardial deformation and afterloads using LV strain combined with the non-invasive estimation of LV pressure. The aim of this study was to perform an echocardiographic assessment in pts with advanced HFrEF before and after infusion of Levosimendan in a chronic setting, using GLS and LVMWI. Methods and results: 6 pts with ischaemic HFrEF were prospectively enrolled in the study. Echo-data were collected from all patients using a Vivid E95 system (GE Healthcare), before and after the end of infusion (24–48 h). Moreover, 4 pts underwent another echo evaluation 96 h after the infusion to assess the long term effect of OR-1896. Although mean end-diastolic volume decreased after 24–48 h, increased after 96 h, as reported in Table 1. As to the Ejection Fraction (EF), strain-parameters and stroke volume (SV) remain unchanged before and after the infusion. Similarly LVMWI-derived parameters also remain overall unchanged (Table 1 ). Conclusions: In pts with ischaemic HFrEF undergoing periodical infusion of Levosimendan, we very preliminary observed a reduction of LV size short after the infusion, which interestingly do not persist after 96 h. The other considered echocardiographic parameters (EF, SV, strain-derived parameters) did not show significant differences before and after the infusion. An explanation is that Levosimendan improves LV congestion but not the contractile force in pts with advanced HFrEF, whose myocardial performance is too compromised. Therefore the haemodynamic benefits observed chronically in pts with Levosimendan might be due to the initial decongestion and its vasodilatory effect, and it may not persist in mid-term, depending on basal myocardial conditions. Larger studies should be conducted to conferm these findings.